2016
DOI: 10.4038/cjs.v45i2.7386
|View full text |Cite
|
Sign up to set email alerts
|

Within variety flowering time variation leads to yield variation in Sri Lankan traditional rice “Sudu wee”

Abstract: Sri Lankan traditional rice is an important breeding resource for development of rice for ecological adaptation during the era of climate change. There are around 2000 accessions belonging to more than 500 varieties comprised of one to several accessions in each with wider morphological differences, flowering times and yield variations. Genetic identity of Sri Lankan traditional rice accessions belonging to each rice variety is not established at molecular level. Variety Sudu wee comprises of around 30 accessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Delayed flowering time increased the vegetative growth and reduced the grain size (Table 5). Similar observations were reported for Sulai, Sudu wee and Hondarawala varieties, where there were positive relationships between DF and vegetative growth characteristics, while negative relationships existed between DF and yield components (Rathnathunga et al 2013;Rathnathunga et al 2015;Rathnathunga et al 2016b;Rathnathunga et al 2016c). In contrast, relationship between DF and yield components of photoperiod responsive 43 Ma wee accessions of Sri Lankan traditional rice was positive under inductive short day season (Pushpakumari et al 2017).…”
Section: Variation Among Accessions Of Sri Lankan Traditional Rice Vasupporting
confidence: 59%
See 2 more Smart Citations
“…Delayed flowering time increased the vegetative growth and reduced the grain size (Table 5). Similar observations were reported for Sulai, Sudu wee and Hondarawala varieties, where there were positive relationships between DF and vegetative growth characteristics, while negative relationships existed between DF and yield components (Rathnathunga et al 2013;Rathnathunga et al 2015;Rathnathunga et al 2016b;Rathnathunga et al 2016c). In contrast, relationship between DF and yield components of photoperiod responsive 43 Ma wee accessions of Sri Lankan traditional rice was positive under inductive short day season (Pushpakumari et al 2017).…”
Section: Variation Among Accessions Of Sri Lankan Traditional Rice Vasupporting
confidence: 59%
“…Comparatively similar PCs were identified in studies of Sulai, Sudu wee and Hondarawala varieties, which suggested the fact that same character standards applied in all genetic diversity studies of Sir Lankan rice (Rathnathunga et al 2015;Rathnathunga et al 2016b;Rathnathunga et al 2016c) (Table 2). Pachchaperumal accessions of 8827, 3408, 3752, 5548, 5550, 5547 and 9047 of cluster one, 5546, 3946, 6834 and 5549 of cluster two, accession of 5383 of cluster three were grouped into…”
Section: Genetic Diversity Of Pachchaperumal and Suduru Samba Accessimentioning
confidence: 60%
See 1 more Smart Citation